PEMBERDAYAAN EKONOMI KOPERASI BERBASIS SYARIAH PADA KPRI SMAN I KOTA SOLOK - Afrizul Afrizul (IAIN Batusangkar, 2020)
In this article there are three things that become problems, namely about how forms of empowerment, the form of savings and credit business is seen in the sharia perspective and what are the inhibiting factors in sharia-based economic empowerment at the head of KPRI SMAN I Kota Solok. The type of research conducted is field research by using a qualitative approach. The purpose of the research is to find out the forms of empowerment of savings and loan business forms seen in the perspective of sharia what are the inhibiting factors in sharia-based economic empowerment at the head of KPRI SMAN I Kota Solok. Data collection techniques are document and documentation interviews he continued analyzing the data needed with various theoretical basis then read and study. The results of this research shown that Sharia-based forms of empowerment at KPRI Syariah SMAN I Solok City. First, cooperatives have been managed by sharia patterns. Second, savings and loans and Islamic financing that have been given to members have reached Rp. 70,000,000, - (Seventy Million Rupiah). Third, by services / ujrah / ratio / fee of 0.8 agreed with members in each savings and loan and Islamic financing. Fourth, increasing understanding and ability of management and members in managing the cooperative through syariah pattern. Fifth, participating in activities carried out by DEKOPINDA of Solok Regency, at Solok Cooperative and Industry Office and centre of KPRI in West Sumatra Province. Sixth, distributing social funds, rewards for children’s members who have good achievements and productive zakat for the surrounding community.